Bibliometric analysis of green finance and climate change in post-Paris Agreement era - Martin Kamau Muchiri; Szilvia Erdei-Gally; Mária Fekete-Farkas; Zoltán Lakner (Journal of Risk and Financial Management, 2022)
Climate change is undeniably one of the long-term challenges confronting humanity across the globe. Various nations have taken initiatives that help reduce greenhouse gas emissions to the environment as well as accelerate financial flows to clean and sustainable projects. The paper provides an overview of green finance after the Paris Agreement by adopting a bibliometric analysis of the selected literature. The study reviewed the literature from the Web of Science database between 2015 and 2022. Data cleaning, formatting, and analysis was performed using VOSviewer and R-studio. Our study indicates increased scholarly interest on the issue of green financing. Most scientific research has been published in climate policy and sustainability journals but lacks mainstream interest in economic and finance journals. Based on our results, it is recommended that further studies on green financing be carried out from the economic and financial perspective using quantitative approaches to supplement the existing literature and provide a wider view to policy makers and regulators.
Keywords: 650; Paris Agreement; VOSviewer; climate change; co-citation; co-occurrence; green financing; green investments; plot analysis; R-studio